THE ROLE OF MICRONUTRIENTS AND SUPPLEMENTS IN HYPOTHYROIDISM MANAGEMENT: A LITERATURE REVIEW - Zuzanna Wróbel; Katarzyna Torbacka; Joanna Kaczor; Maja Torbacka; Katarzyna Rozkosz; Natalia Wróbel; Olga Jakubik; Patrycja Podlejska; Aleksandra Sosin; Wojciech Bednarz (International Journal of Innovative Technologies in Social Science, 2025)
Background: Despite standard levothyroxine (LT4) therapy, many patients with hypothyroidism continue to report persistent symptoms such as fatigue, cognitive impairment, and reduced quality of life. This has prompted growing interest in adjunctive therapies, particularly micronutrients and supplements, which may modulate immune function and thyroid gland metabolism. Aim: To evaluate the clinical impact of vitamin D, selenium, zinc, myo-inositol, and synbiotic supplementation in hypothyroid patients—especially those with autoimmune thyroiditis and subclinical hypothyroidism—by analyzing their effects on thyroid function, antibody titers, and patient-reported outcomes. Materials and methods: A systematic literature search was conducted predominantly in PubMed and related biomedical databases. The review included randomized controlled trials (RCTs), systematic reviews, and relevant observational studies published between 2015 and 2025. Studies were analyzed for their findings on selected micronutrients and their influence on biochemical markers (TSH, FT4, FT3, anti-TPO, anti-Tg), immune modulation, and quality of life parameters. Results: Adjunctive supplementation with micronutrients such as selenium, vitamin D, zinc, myo-inositol, and synbiotics shows potential clinical benefits in hypothyroidism management. These include reductions in thyroid autoantibody levels, improvements in thyroid hormone profiles, and better patient-reported outcomes. Synergistic effects were noted particularly for combined regimens, though results varied by baseline nutrient status and study design. Conclusions: Supplementation with selected micronutrients may provide meaningful support in managing hypothyroidism, particularly in patients with residual symptoms despite LT4 therapy. However, larger multi-center RCTs are needed to confirm efficacy, establish optimal dosing, and identify patient subgroups most likely to benefit.